تقدير قوة الهجين لبعض الصفات الإنتاجية لهجن من الذرة الصفراء (Zea mays) تحت ظروف العدوى الصناعية بحفار ساق الذرة الكبير Sesamiacretica (مجلة جامعة اللاذقية- سلسلة العلوم البيولوجية, 2016)
This study was conducted at the of field research station Sianow belong to the General Commission for Scientific Agricultural Research at Lattakia, to evaluate the susceptibility of maize hybrids produced by using half Diallel the cross according to the design ofrandomized completeblocks (R.C.B.D), under industrial infection by large corn stem borer Sesamia cretica. Hybrids were compared with the control (Ghouta- 82).The hybrid (P1 × P2) Showed positive and highly significantheterosis for Ear diameter and tolerance forlarge corn stem borer compared with the average of the parents and the best parents and the check (Ghouta- 82). The hybrid (P2 × P6) showed positive and highly significant heterosis for the number of kernels per row compared with the average of the parents and the best parents and the check (Ghouta- 82). Also the hybrid (P1 × P6) showed positive and highly significant heterosis for the number of kernels per row relative to the average of the parents and the best parents and the check (Ghouta- 82). hybrid (P4 × P6) showed positive and highly significant heterosis for the recipe grain yield compared with the average of the parents and the best parents and the check (Ghouta- 82). The hybrid(P5 × P6) also showed positive and highly significant heterosis for the Percentage of dead hearts of the developing summit compared with the average of the parents and the best parents, and compared with the check (Ghouta- 82), therefore it can be considered as a sensitive hybrid.أجري هذا البحث في حقول محطة بحوث سيانو التابعة للهيئة العامَّة للبحوث العلميَّة الزراعيَّة في اللاذقيَّة, بهدف تقويم حساسيَّة خمسة عشر هجيناً من الذُّرة الصَّفراء الناتجة عن التهجين نصف التبادلي وفق تصميم القطاعات العشوائيَّة الكاملة, للإصابة بحَفار ساق الذُّرة الكبير Sesamia cretica Led. تحت ظروف العَدوى الصناعيَّة، ومقارنتها مع الشاهد (غوطة82-). أظهر الهجين (P1×P2) قوّة هجين موجبة، وعاليَّة المعنوية بالنسبة إلى صفة قَطر العرنُوس،ولصفة التحمل لحشرة حفار الساق قياساً إلى متوسِّط الأبوين، وأفضل الأبوين، وصنف المقارنة غوطة82-. وأظهر الهجين (P2×P6) قوّة هجين موجبة، وعاليَّة المعنوية بالنسبة إلى صفة عَدد الصُّفوف بالعرنُوس قياساً إلى متوسِّطالأبوين، وأفضل الأبوين، وصنف المقارنة غوطة.82-كما أظهر الهجين (P1×P6) قوّة هجين موجبة، وعاليَّة المعنوية بالنسبة إلى صفة عَدد الحُبُوب بالصَّف قياساً إلى متوسِّطالأبوين، وأفضل الأبوين، وصنف المقارنة غوطة82-. وأظهر الهجين (P4×P6) قوّة هجين موجبة، وعاليَّة المعنوية بالنسبة إلى صفة الغلَّة الحبيَّة السَّليمة قياساً إلى متوسِّط الأبوين،وأفضل الأبوين، وصنف المقارنة غوطة82-. كما أظهر الهجين (P5×P6) قوّة هجين موجبة، وعاليَّة المعنوية بالنسبة إلى صفة النسبة المئويَّة لمَوت القمَّة الناميَّة قياساً إلى متوسِّط الأبوين، وأفضل الأبوين، وصنف المقارنة غوطة82-؛ لذا يمكن عدّه هجيناً حساساً.